Real Space Visualization of Entangled Excitonic States in Charged Molecular Assemblies - Doležal, Jiří; Canola, Sofia; Hapala, Prokop; de Campos Ferreira, Rodrigo Cezar; Merino, Pablo; Švec, Martin (ACS nano, 2022)
Entanglement of excitons holds great promise for the future of quantum computing, which would use individual molecular dyes as building blocks of their circuitry. Studying entangled excitonic eigenstates emerging in coupled molecular assemblies in the near-field with submolecular resolution has the potential to bring insight into the photophysics of these fascinating quantum phenomena. In contrast to far-field spectroscopies, near-field spectroscopic mapping permits direct identification of the individual eigenmodes, type of exciton coupling, including excited states otherwise inaccessible in the far field (dark states). Here we combine tip-enhanced spectromicroscopy with atomic force microscopy to inspect delocalized single-exciton states of charged molecular assemblies engineered from individual perylenetetracarboxylic dianhydride (PTCDA) molecules. Hyperspectral mapping of the eigenstates and comparison with calculated many-body optical transitions reveals a second low-lying excited state of the anion monomers and its role in the exciton entanglement within the assemblies. We demonstrate control over the exciton coupling by switching the assembly charge states. Our results reveal the possibility of tailoring excitonic properties of organic dye aggregates for advanced functionalities and establish the methodology to address them individually at the nanoscale.
Keywords: exciton; AFM; STM-induced luminescence; PTCDA; delocalization; entanglement; STML